(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2021)
From the beginning of civilization and in several cultures, people established a strong connection with animals and in many cultural traditions they have imbued them with a symbolic value. A good knowledge of the species of fauna and flora of a certain place, allows us to understand the importance of their protection and conservation, which will greatly help to face one of the main problems of humanity on a global scale: the loss of biodiversity. In recent years in Uruguay there has been an increase regarding the knowledge of the species that make up our native fauna. Although this information is recognized and accessible within the scientific-academic field, it is often not known by the rest of the population. The objective of this work is to evaluate the current state of knowledge of the fauna of native tetrapod vertebrates in the Uruguayan population, which was done through a semi-structured survey of 593 people. The results obtained showed a scarce knowledge of our fauna, a fact that has been seen in other countries. We discuss the challenge of implementing actions and strategies that favor the knowledge about it in the population.